Proteome profiling of heat, oxidative, and salt stress responses in Thermococcus kodakarensis KOD1 - Jia, Baolei; Liu, Jinliang; Van Duyet, Le; Sun, Ying; Xuan, Yuan H.; Cheong, Gang-Won (Frontiers in Microbiology, 2015)
The thermophilic species, Thermococcus kodakarensis KOD1, a model microorganism for studying hyperthermophiles, has adapted to optimal growth under conditions of high temperature and salinity. However, the environmental conditions for the strain are not always stable, and this strain might face different stresses. In the present study, we compared the proteome response of T. kodakarensis to heat, oxidative, and salt stresses using two-dimensional electrophoresis, and protein spots were identified through MALDI-TOF/MS. Fifty-nine, forty-two, and twenty-nine spots were induced under heat, oxidative, and salt stresses, respectively. Among the up-regulated proteins, four proteins (a hypothetical protein, pyridoxal biosynthesis lyase, peroxiredoxin, and protein disulphide oxidoreductase) were associated with all three stresses. Gene ontology analysis showed that these proteins were primarily involved metabolic and cellular processes. The KEGG pathway analysis suggested that the main metabolic pathways involving these enzymes were related to carbohydrate metabolism, secondary metabolite synthesis, and amino acid biosynthesis. These data might enhance our understanding of the functions and molecular mechanisms of thermophilic Archaea for survival and adaptation in extreme environments.